Current treatment of hypoparathyroidism: Theory versus reality waiting guidelines for children and adolescents - Di Maio, Salvatore; Soliman, Ashraf T; De Sanctis, Vincenzo; Kattamis, Christos C (Acta Biomedica Atenei Parmensis, 2018)
The diagnosis of hypoparathyroidism(HPT)is readily made in the presence of hypocalcemia with markedly reduced or absent parathormone (PTH) levels. Currently available treatments for HPT include high dose vitamin D (ergocalciferol, D2 and cholecalciferol, D3) or, the active metabolite dihydroxy vitamin D (calcitriol), in addition to calcium supplements.This regimen, if not well monitored, can lead to hypercalciuria, as PTH deficiency impairs renal calcium reabsorption. Thus the goal of treatment, is to maintain serum calcium at the low end of the normal range. Undertreatment can cause symptomatic hypocalcemia, while overtreatment hypercalciuria, which may lead to nephrolithiasis, nephrocalcinosis, and renal insufficiency. At present, there is no consensus on the management of HPT in children and adolescents and only few studies are available on the long term outcome of patients with recombinant HPT treatment. The purpose of this article is to review, in a comprehensive manner, the major aspects of HPT management in children and adolescents waiting for authoritative guidelines for the treatment of HPT in this group of patients. Further research, addressing specific questions for this population are urgently needed to improve long-term safety of patients. Educational interventions are also needed for professionals, parents and patients to enable them to improve knowledge, quality of life and effective management care at home.